KAJIAN STABILITAS BENDUNGAN JLANTAH KONDISI SURUT CEPAT DENGAN METODE ELEMEN HINGGA - Agung Ariyan Putra; Sri Prabandiyani Retno Wardani; Kresno Wikan Sadono (LPPM Universitas Abdurrab, 2025)
The Jlantah Dam is a random fill dam with a vertical core zone. One of the potential hazards of the Jlantah Dam is slope failure caused by the rapid drawdown of the reservoir water level. During a rapid drawdown event, the pore water pressure does not decrease in tandem with the rapid drop in water level. This condition can be a critical factor in slope stability due to the pore water pressure within the dam body. This study aims to analyze the stability of the Jlantah Dam under rapid drawdown conditions using three daily water level reduction scenarios: 2.3 m/day (10 days), 1 m/day (23 days), and 0.75 m/day (31 days). The rapid drawdown is conducted from the normal water level (+685) to the minimum water level (+662), with a total elevation drop of 23 meters. The analysis results show that the percentage reduction in pore water pressure under rapid drawdown conditions is 48.673% for the 2.3 m/day (10 days) scenario, 57.979% for the 1 m/day (23 days) scenario, and 60.309% for the 0.75 m/day (31 days) scenario. The minimum safety factors obtained for each scenario are 1.74023, 1.67292, and 1.6783, respectively. These values remain above the acceptance criteria for stability during rapid drawdown from normal to minimum water levels.